Analisis Perbandingan Pembentukan Komponen Cadangan Dengan Wajib Militer Korea Selatan Sebagai Upaya Bela Negara Dalam Sistem pertahanan Dan Keamanan Negara (International Forum of Researchers and Lecturers, 2023)
The 1945 Constitution of the Republic of Indonesia stipulates that Indonesian citizens must participate in efforts to defend the country. This is contained in article 27 paragraph 3 which reads,